1799 Ky. Acts 7 - (:unkn) unknown (My University, 1799)
An Act to Amend an Act Entitled "An Act Concerning the Militia," p. 421-22,§ 1-3: [T]he brigadier generals shall attend each regimental muster within their brigades to view the same; it shall be the duty of the brigade major, attended by the commandant of the regimnt, to inspect the same at every muster.§ 2. All fines arising within the bounds of any regiment, on account of delinquencies of officers, privates, or otherwise, shall be appropriated to the use of such regiment only.§ 3. . . . [E]ach non-commissioned officer shall have ten days notice of each muster; and each non-commissioned officer and private, appearing on parade without a gun after being duly notified, shall be fined any sum not exceeding fifty cents, at the discretion of a court martial.
Keywords: ARMED FORCES